The More, the Merrier? Interest Groups and Legislative Change in the Public Hearings of the German Parliamentary Committees. Issue 2 (3rd April 2017) - Eising, Rainer; Spohr, Florian
Abstract : The article examines the impact of organised interests on the passage of legislation in the German Bundestag through an empirical analysis of the position papers presented in the public hearings of its standing committees in 2011. These committees are the most important forums to revise legislative proposals. Drawing on resource dependency theory, we employ GLM regression analyses to study if interest groups act as change agents that bring legislation closer to their own policy preferences. Controlling for institutional and bill characteristics, we discuss two major findings that shed light on the role of interest groups in legislation. First, business groups' opposition to government bills triggers legislative changes because their members control the means of production and make investment decisions. In contrast, fundamental opposition of non-business groups has no impact. Second, bills debated and opposed by a greater number of interest groups undergo more changes pointing to the importance of the density of interest groups and balance of opinions on a proposal.